Single-nucleotide polymorphisms in the TSPYL-4 and NT5DC1 genes are associated with susceptibility to chronic obstructive pulmonary disease - GUO, YI; GONG, YI; SHI, GUOCHAO; YANG, KUN; PAN, CHUNMING; LI, MIN; LI, QINGYUN; CHENG, QIJIAN; DAI, RANRAN; FAN, LIANG; WAN, HUANYING (Molecular medicine reports, 2012)
The risk of developing chronic obstructive pulmonary disease (COPD) is partially determined by genetic and environmental factors. Many published candidate gene studies show conflicting results due to ethnic differences and sample sizes. The number of these studies carried out in Chinese populations is small. To investigate candidate genes and haplotypes for susceptibility to COPD in a southern Han Chinese population, we performed genotyping of DNA samples in 200 COPD patients and 250 control subjects by analyzing 54 single-nucleotide polymorphisms (SNPs) in 23 genes associated with the development of COPD and/or pulmonary function identified by genome-wide association studies (GWAS). We also performed linkage disequilibrium (LD) and haplotype analysis according to the results of genotyping. The frequencies of the SNP [rs3749893 of testis-specific protein Y-encoded-like 4 (TSPYL-4) gene] G allele and SNP [rs1052443 of 5′-nucleotidase domain containing 1 (NT5DC1) gene] A allele were significantly higher in the cases studied compared to the control subjects (P=0.032, P<0.05, OR=0.692, 95% CI 0.495-0.970; P=0.0205, P<0.05, OR=0.670, 95% CI 0.477-0.941, respectively). Results showed that two blocks of SNPs (rs1052443 and rs3749893; rs11155242 and rs6937121) had sufficient precision to allow construction of a haplotype block. We constructed the TSPYL-4 and NT5DC1 haplotypes of the cases and controls, but no significant difference between the two groups was found. rs3749893 A allele of TSPYL-4 and rs1052443 C allele of NT5DC1 were associated with a protective effect against the deterioration of pulmonary function. In conclusion, TSPYL-4 and NT5DC1 gene polymorphisms are associated with susceptibility to COPD and pulmonary function.